Associations of atopic dermatitis and asthma with child behaviour: Results from the PROBIT cohort. Issue 9 (9th June 2019) - Ballardini, Natalia; Kramer, Michael S.; Oken, Emily; Henderson, Alexander John; Bogdanovich, Natalia; Dahhou, Mourad; Patel, Rita; Thompson, Jennifer; Vilchuck, Konstantin; Yang, Seungmi; Martin, Richard M.; Flohr, Carsten
Abstract: Background: Conflicting findings from studies evaluating associations of allergic disease with child behaviour require longitudinal studies to resolve. Objective: To estimate the magnitude of associations of atopic dermatitis (AD) in infancy, and symptoms of asthma and AD at 6.5 years, with child behaviour at 6.5 years. Methods: Secondary cohort analysis of the Promotion of Breastfeeding Intervention Trial (PROBIT). PROBIT enrolled 17 046 infants at birth and followed them up at 6.5 years (n = 13 889). Study paediatricians collected data on infantile AD at repeated follow‐up examinations during the first year of life. At 6.5 years, paediatricians performed skin prick tests and parents reported asthma and AD symptoms during the prior year. In addition, parents and teachers completed the Strength and Difficulties Questionnaire, which includes scales on hyperactivity/inattention, emotional problems, conduct problems, peer problems and prosocial behaviours. Results: Physician‐diagnosed AD in the first year of life was not associated with increased risk for behavioural problems at 6.5 years. Emotional problems at 6.5 years were more common among children with AD symptoms (OR: 2.24, 95% CI: 1.62‐3.12) and asthma symptoms (OR: 1.45; 95% CI: 1.07‐1.96) during the past year at 6.5 years and ORs for children with symptoms of more severe AD and asthma were also higher. AD in the past year was also associated with probable hyperactivity/inattention disorder at 6.5 years (OR: 2.05; 95% CI: 1.09‐3.84). Other subscales of the SDQ were not related to asthma or AD symptoms during the past year. Conclusions and clinical relevance: Children with AD symptoms were at higher risk for concomitant hyperactivity/inattention and emotional disorder, and children with asthma symptoms were at higher risk of having concomitant emotional problems. However, AD during infancy did not predict childhood behaviours.